THE INTRODUCTION OF NEW TECHNOLOGIES AND INNOVATIONS INTO THE ECONOMIC LIFE OF THE OASIS POPULATION - Iskandarov Sherzod Abduganievich; Otabek Tursunovich Ro'ziev (Western European Studies, 2025)
Since the emergence of humanity, it is distinguished by the fact that, over a long historical period, under the influence of various natural and geographical factors, the specific local characteristics of each people have been preserved. During the period under study, there were a number of customs and rituals associated with holding traditional weddings in the oasis, such as the birth of a child, the cradle wedding, the circumcision wedding, the marriage wedding, and the wedding of the prophet's age.
Keywords: wedding; emergence; characteristics